How balance task-specific training contributes to improving physical function in older subjects undergoing rehabilitation following hip fracture: a randomized controlled trial. (March 2018) - Monticone, Marco; Ambrosini, Emilia; Brunati, Roberto; Capone, Antonio; Pagliari, Giulia; Secci, Claudio; Zatti, Giovanni; Ferrante, Simona
Objective: To evaluate the efficacy of a rehabilitation programme including balance task-specific training in improving physical function, pain, activities of daily living (ADL), balance and quality of life in subjects after a hip fracture. Design: Randomized controlled trial. Subjects: A total of 52 older subjects selected for internal fixation due to extra-capsular hip fracture were randomized to be included in an experimental ( n = 26) and control group ( n = 26). Interventions: The experimental group underwent a rehabilitation programme based on balance task-specific training. The control group underwent general physiotherapy, including open kinetic chain exercises and walking training. Both groups individually followed programmes of 90-minute sessions five times/week for three weeks. Outcome measures: The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), a Pain Numerical Rating Scale, the Berg Balance Scale, the Functional Independence Measure and the 36-item Short-Form Health Survey. The participants were evaluated before and after training, and after 12 months. Results: Significant effects of time, group and time × group were found for all outcome measures in favour of the experimental group. A clinically important between-group difference of 25 points was achieved after training and at follow-up in terms of the primary outcome (WOMAC function before treatment, after treatment and at follow-up was 84.8 (3.7), 39.8 (4.9) and 35.7 (6.2) for the experimental group and 80.9 (5.7), 65.2 (7.1) and 61.0 (11.1) for the control group). Conclusion: An inpatient rehabilitation programme based on balance task-specific training is useful in improving physical function, pain, ADL and quality of life in older patients after hip fracture.